Leucocytosis and Asymptomatic Urinary Tract Infections in Sickle Cell Patients at a Tertiary Hospital in Zambia - Taonga Musonda; Mildred Zulu; Mulemba Samutela; Annie Kalonda; Hamakwa Mantina; Pauline Okuku; Musalula Sinkala; Panji Nkhoma (Anemia)
Sickle cell anaemia (SCA) is an inherited disease resulting from mutations in the β-globin chain of adult haemoglobin that results in the formation of homozygous sickle haemoglobin. It is associated with several complications including an altered blood picture and damage in multiple organs, including the kidneys. Kidney disease is seen in most patients with SCA and may affect glomerular and/or tubular function, thereby putting these patients at risk of urinary tract infections. However, there is a paucity of data on the prevalence of urinary tract infections (UTIs) among SCA patients in Zambia. This study aimed to determine the prevalence of UTIs and haematological and kidney function profiles among SCA patients at the University Teaching Hospitals, Lusaka, Zambia. This was a cross-sectional study conducted between April and July 2019 involving 78 SCA patients who presented at the UTH. Blood and midstream urine samples were collected from each participant using the standard specimen collection procedures. Full blood counts and kidney function tests were determined using Sysmex XT-4000i haematology analyser and the Pentra C200 by Horiba, respectively. Bacterial profiles of the urine samples were determined using conventional microbiological methods. We found that all the measured patients’ haemoglobin (Hb) levels fell below the WHO-recommended reference range with a minimum of 5 g/dl, a maximum of 10.5 g/dl, and a mean of 8 ± 1 g/dl. Fifty percent of the participants had moderate anaemia, while the other 50% had severe anaemia. The minimum WBC count of the participants was 0.02 × 109/L with a maximum of 23.36 × 109/L and a mean of 13.48 ± 3.87 × 109/L. Using the one-way analysis of variance test, we found no significant difference in mean WBC count and Hb concentration across various age-group categories that we defined. Bacteriuria was found in 25% of participants. The most common bacterial isolates were Staphylococcus aureus (32%) and coagulase-negative Staphylococci (32%). Klebsiella pneumoniae was 16%. We found no significant association between bacterial isolates and white blood cell count, age groups, sex, and anaemia severity p=0.41. None of the participants were diagnosed with kidney disease. There was a high prevalence of asymptomatic UTIs among SCA patients at UTH, which, when coupled with the marked leukocytosis and anaemia, may negatively impact the clinical outcome of the patients. Therefore, we recommend close monitoring of sickle cell patients in Zambia for such conditions to improve patients’ outcomes.